Analysis on the Livelihood Vulnerability of Lift Net Fisher Households, Tapanuli Tengah, Sumatera Utara - Tirta Anugerah; Shofian Nanda Adiprayoga (International Journal of Marine Engineering Innovation and Research, 2023)
Fishermen are a group of people whose livelihood is very dependent on the condition of the marine ecosystem. Ecological damage in their waters caused by the impact of climate variability and illegal fishing activities causes their livelihoods to be threatened. This research uses a mixed research approach, namely quantitative and qualitative. Quantitative data was obtained through surveys of respondents with the help of questionnaires while qualitative data was obtained through in-depth interviews. The research found that lift net fishing households were in a vulnerable condition with a value of +0.23. This research also reveals that fishing households implement natural resource-based and non-natural resource-based livelihood strategies. These efforts are made so that fishermen can live and exist in society.